Terapi Gabapentin pada Pasien Herpes Zoster Oftalmikus Fase Akut: Neuralgia Paska Herpetika - Iffat Taqiyah; Hendra Tarigan Sibero (CV. Jasa Sukses Abadi, 2020)
Herpes zoster (HZ) is one of skin disease caused by viral infection, characterized by rash and pain, developed within unilateral dermatome consequence by Varicella Zoster Virus (VZV) reactivation in infected nerve. One of complication of HZ is pain that persists after the rash dissappears called postherpetic neuralgia (PHN). Postherpetic neuralgia can be predicted by people aged more than 50 years, severe prodromal symptoms, and severe acute pain of HZ. No treatment of prevention therapy for PHN has been shown but early therapy for reducing pain is expected for better outcome. Theory of early therapy of PHN has been still questionable. A 73-years old- women presenting with multiple blisters on her right forehead and eyelid accompanied by pain since 4 days ago. Dermatological status region of orbitalis and frontalis dextra, ophtalmic division of trigeminal nerve level appears pustules with erythematous base, circumscript, multiple, regular, lenticular, confluence, zoosteriform. Diagnosis of this case is herpes zoster ophtalmicus dextra. Management of this case is Acyclovir 5x800 mg for 7 days, Gabapentin 2x300 mg for 7 days, and compress with NaCl 0,9%. Patient has better outcome and patient has PHN that persist 5 months after rash dissappears. In this case, Gabapentin therapy in the acute phase can not prevent PHN but has a good outcome for reducing pain.